East-to-west genetic structure in populations of Aechmea calyculata (Bromeliaceae) from the southern Atlantic rainforest of Brazil - Goetze, Marcia; Palma-Silva, Clarisse [UNESP]; Zanella, Camila Martini; Bered, Fernanda (Wiley-Blackwell, 2016)
The Brazilian Atlantic rainforest is the second largest tropical humid forest in South America. Most phylogeographical studies conducted so far have focused on taxa with a north-to-south pattern of geographical distribution in the Atlantic rainforest. In the present study, we focused on Aechmea calyculata, a species with an east-to-west pattern of occurrence in the southern portion of the Atlantic rainforest. We analysed the genetic diversity and structure of A.calyculata using 12 nuclear microsatellites (simple sequence repeats, SSRs), two intergenic plastid DNA spacers and the nuclear gene phytochrome C (phyC). Results revealed high genetic structure across the distribution of A.calyculata, especially between populations in the western and eastern regions. However, no apparent geographical barrier isolates these two groups today, suggesting a historical process of vicariance. This pattern was probably associated with vegetation shifts that occurred during the Pleistocene, with grasslands acting as a barrier to gene flow. Genetic diversity was evenly distributed among A.calyculata populations with SSR and plastid DNA and concentrated in the eastern region when phyC was considered. Signs of demographic population growth in the eastern group were detected for A.calyculata. Our results support the findings of other studies, which also found populations with high genetic diversity occurring in the southern portion of the Atlantic rainforest.
Keywords: bromeliads; cpDNA; genetic diversity; haplotypes; microsatellites; mixed forests; ombrophilous forests; phyC; semi-deciduous forests